(untitled) (Altre Modernità, 2018)
“Melancholic universalism” is a retrospective journey in Sara Ahmed’s work. In this work, the author deploys her critiques to false universalisms that prevail in contemporary thought. Departing from a critique to the debate on identity politics and its caricaturizing set by philosophers such as Zizek or Badiou, it follows with a false acceptation of non-heterosexual ways of social reproduction and it ends up with a critical reflection on Kristeva’s work about “the problem of the Muslim veil” in France. The text argues that what is normally considered as universal demands the disavowal of certain specific embodied differences in order to attain an alleged “impartiality”. Some bodies are considered to be the retainers of this impartiality and therefore, it shows that universalism holds a bias in terms of gender, race and sexuality. Therefore, universalisms is always a false concept as it requires a melancholic gesture, a gesture of loss and grieving, to the subjects that are not white, heterosexual and cis males. “Universalismo melancólico” es un recorrido retrospectivo por la obra de Sara Ahmed en la que se sientan las bases para la crítica a los falsos universalismos que imperan en el pensamiento contemporáneo. Iniciando con una crítica al debate sobre las políticas de la identidad y su caricaturización por parte de filósofos como Zizek o Badiou, prosigue con la falsa aceptación de modos no heterosexuales de reproducción social y finaliza con una reflexión crítica de la mano de Kristeva y el “problema del velo musulmán” en Francia. El texto arguye que aquello que se considera universal es, en realidad, la exigencia de abandonar ciertas diferencias connotadas y encarnadas en aras a una supuesta “imparcialidad” con un sesgo de género, raza y orientación sexual. De hecho, algunos cuerpos son considerados obstaculizadores de dicha imparcialidad. Por tanto, el unviersalismo es, en realidad, falso universalismo ya que demanda un gesto melancólico, de pérdida, a los sujetos que no sean blancos, heterosexuales y hombres cis